Administrative Growth and Grant Payouts in Nonprofit Foundations: Fulfilling the Public Good amid Professionalization?. (8th August 2014) - Stewart, Amanda J.; Faulk, Lewis
<x xml:space="preserve">Abstract</x> The Tax Reform Act of 1969 remains the core governing policy for the U.S. foundation sector, primarily for its qualifying distributions mandate, which ensures a baseline spending of foundation assets toward charitable purposes. However, implementation of this policy required additional foundation administrative resources and contributed to significant professionalization of the foundation sector. This article focuses on the payout requirement's potential paradox of accountability, as administrative expenses can be counted toward fulfilling foundations' qualifying distributions. Using a 14‐year panel of grantmaking foundations, the analysis seeks to understand whether professionalization, measured by operating and administrative expenses, contributes to or crowds out grantmaking. Findings indicate that professionalization of the foundation sector has a small yet practically and statistically significant positive association with foundation grantmaking. From a policy perspective, the current structure of the qualifying distributions mandate does not appear to lead to a crowding out of grant allocations as administrative expenses grow.